2021
DOI: 10.3892/mmr.2021.12482
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‑induced dysfunction of energy metabolism in the heart results in the fibrosis of cardiac tissues

Abstract: Thoracic radiotherapy increases the risk of radiation-induced heart damage (riHd); however, the molecular mechanisms underlying these changes are not fully understood. The aim of the present study was to investigate the effects of radiation on the mouse heart using high-throughput proteomics. Male c57Bl/6J mice were used to establish a model of riHd by exposing the entire heart to 16 Gy high-energy X-rays, and cardiac injuries were verified using a cardiac echocardiogram, as well as by measuring serum brain na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…To support this hypothesis, it was shown that cardiac mitochondrial respiratory capacity was reduced 40 weeks after cardiac irradiation in mice at 2 Gy [ 36 ]. Note that this was confirmed in a recent study in mice after heart irradiation at 16 Gy which induces an increase in extracellular matrix proteins and variation in metabolism-related proteins detectable after 5 months, a time similar to that used in our study [ 23 ]. Dysregulation of the metabolism status with modification of ATP levels may impact TRPM4 in two different ways.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To support this hypothesis, it was shown that cardiac mitochondrial respiratory capacity was reduced 40 weeks after cardiac irradiation in mice at 2 Gy [ 36 ]. Note that this was confirmed in a recent study in mice after heart irradiation at 16 Gy which induces an increase in extracellular matrix proteins and variation in metabolism-related proteins detectable after 5 months, a time similar to that used in our study [ 23 ]. Dysregulation of the metabolism status with modification of ATP levels may impact TRPM4 in two different ways.…”
Section: Discussionsupporting
confidence: 90%
“…This is a specificity of our study since a recent review reported that among 159 studies using models of irradiation-induced cardiac remodeling in rodents, only 4% targeted a restricted area of the heart while others undertook whole heart or whole animal irradiation [ 26 ]. Some of these studies in mice with specific irradiation of the heart revealed an increase in fibrosis detected by Masson trichrome staining, observed at 5 months at the ventricular level [ 23 , 25 ], which was also reported in rats [ 27 ]. Interestingly, in our study, we did not observe such fibrosis neither at the ventricular level nor at the atrial level, while it was present in valvular structures, consistent with a specific targeting of the valve.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Subsequent subcellular localization and functional enrichment analyses via acetyl-proteomics indicated that DEPs at different acetylated sites were enriched in mitochondrial and energy metabolism. Interestingly, we previously discovered that irradiated heart tissue exhibited significant dysregulation of mitochondrial damage and metabolites [ 38 ]. In addition to the myocardium, radiation-induced mitochondrial damage in the skeletal muscle alters the proteins involved in energy metabolism-related processes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that high-energy X-rays resulted in cardiometabolic disorders, collagen deposition, and suppressed cardiac function [ 38 ]. In this study, we aimed to investigate the mechanisms of radiation-induced cellular senescence, mainly using tandem mass tags- (TMT-) labeled acetylation proteomics.…”
Section: Introductionmentioning
confidence: 99%